Elite youth soccer players' physiological responses, time-motion characteristics, and game performance in 4 vs. 4 small-sided games: The influence of coach feedback. - Brandes, M.; Elvers, S. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this study was to determine the impact of mild vs. strongly pushed coach feedback on the physiological response, ratio of perceived exertion (RPE), and time-motion characteristics in soccer training with small-sided games (SSGs). Sixteen elite youth soccer players (aged 17.2 ± 0.7 years, VO2max 62.1 ± 3.8 ml/kg/min) played two 4 vs. 4 small-sided games each. In random order, the coach provided a mild, unobtrusive, or a strongly pushed feedback throughout the game. Physiological measurements included heart rate expressed in mean values and intensity zones, blood lactate concentration, and RPE. The distance traveled, number of sprints, and work:rest ratio were captured by global positioning systems at 5 Hz. Game performance, such as volume of play and efficacy index, was estimated using the Team Sports Assessment Procedure. No differences were found for the physiological response and time-motion characteristics, but effect sizes demonstrated an increase in RPE (+0.4, p = 0.27) and a decrease in game performance (e.g., volume of play, -2.5, p = 0.08) under pushed feedback. Although a pushed feedback raises RPE, it negatively affected the players' game performance, without necessarily provoking higher physiological responses. These results should help coaches to understand that modifying the type of feedback provided during SSG does not impact the physiological response if SSG are already played with high intensity but that the feedback affects RPE and game performance. To keep a better game performance, soccer coaches are encouraged to provide smooth feedback during SSG.